2009
DOI: 10.1093/cvr/cvp121
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125a-5p partly regulates the inflammatory response, lipid uptake, and ORP9 expression in oxLDL-stimulated monocyte/macrophages

Abstract: MicroRNA-125a-5p may partly provide post-transcriptional regulation of the proinflammatory response, lipid uptake, and expression of ORP9 in oxLDL-stimulated monocyte/macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
221
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(234 citation statements)
references
References 43 publications
9
221
0
4
Order By: Relevance
“…The present study also found that miR-146b-5p may be induced by oxLDL stimulation in a time-and dose-dependent manner, which was consistent with the results of a previous study (13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also found that miR-146b-5p may be induced by oxLDL stimulation in a time-and dose-dependent manner, which was consistent with the results of a previous study (13).…”
Section: Discussionsupporting
confidence: 93%
“…A previous study demonstrated upregulation of miR-146b-5p in oxidized low-density lipoprotein (oxLDL)-stimulated monocytes (13); however, to the best of our knowledge, no further study on the role of miR-146b-5p in AS has been performed. Thus, the present study investigated the potential role of miR-146b-5p in AS and explored the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 86%
“…With the exception of miR-193b, the amplitude of change in the abundance of individual guide strands was less than 2-fold (14). In contrast to the small changes in miRNA expression described in our previous study, several studies have described robust induction of a subset of miRNAs in human monocytes responding to LPS and other inflammatory treatments (15)(16)(17)(18)(19). These observations led us to the important discovery that all activation-associated miRNAs tested had higher basal expression levels in MDMs than in monocytes (14).…”
mentioning
confidence: 62%
“…Our previous studies [24] have shown that some miRNAs are upregulated in oxLDL-stimulated monocytes/macrophages. In this study, the expression of miR-29a is notably upregulated in Table 1 Comparison of inflammatory biomarkers secreted by transfecting the miR-29a inhibitor and mimics and siLPL.…”
Section: Discussionmentioning
confidence: 95%